Involvement of ammonia metabolism in the improvement of endurance performance by tea catechins in mice - Chen, Shu (Sci Rep, 2020)
Blood ammonia increases during exercise, and it has been suggested that this increase is both a central and peripheral fatigue factor. Although green tea catechins (GTCs) are known to improve exercise endurance by enhancing lipid metabolism in skeletal muscle, little is known about the relationship between ammonia metabolism and the endurance-improving effect of GTCs. Here, we examined how ammonia affects endurance capacity and how GTCs affect ammonia metabolism in vivo in mice and how GTCs affect mouse skeletal muscle and liver in vitro. In mice, blood ammonia concentration was significantly negatively correlated with exercise endurance capacity, and hyperammonaemia was found to decrease whole-body fat expenditure and fatty acid oxidation–related gene expression in skeletal muscle. Repeated ingestion of GTCs combined with regular exercise training improved endurance capacity and the expression of urea cycle–related genes in liver. In C2C12 myotubes, hyperammonaemia suppressed mitochondrial respiration; however, pre-incubation with GTCs rescued this suppression. Together, our results demonstrate that hyperammonaemia decreases both mitochondrial respiration in myotubes and whole-body aerobic metabolism. Thus, GTC-mediated increases in ammonia metabolism in liver and resistance to ammonia-induced suppression of mitochondrial respiration in skeletal muscle may underlie the endurance-improving effect of GTCs.